Globicephalinae Gray 1866 - Boessenecker, Robert W. (Zenodo, 2013)
cf. Globicephalinae gen. et sp. indet. REFERRED MATERIAL. — UCMP 219034, a partial right tympanic bulla, collected by R.W. Boessenecker from UCMP locality V99842; UCMP 219162, a partial tooth collected by R.W. Boessenecker from UCMP locality V99833. STRATIGRAPHIC OCCURRENCE. — Middle part of the San Gregorio section of the Purisima Formation, Early Pliocene ( c. 5.6-3.35 Ma; Zanclean-Piacenzian equivalent; Fig. 2). DESCRIPTION Ŋe isolated tooth (UCMP 219162) is missing part of the root, and the tip of the crown was abraded away during life (Fig. 40). While the lingual and labial directions are obvious on this specimen, anterior and posterior are not, and thus it is unclear if it is an upper or a lower tooth. Ŋe conical root is elongate, straight, oval in cross section, and basally tapering (Fig. 40C). Ŋe crown is conical, with smooth enamel, a lingually curved tip, and oval in cross section (Fig. 40A, B). Ŋe crown and root are anteroposteriorly compressed. Ŋe tympanic bulla (UCMP 219034) is missing most of the outer lip as well as the posterior process; it is large for an odontocete (41 mm in length; Table 12). Ŋe involucrum is robust and sinuous in medial view, and anteriorly, the involucrum is inflated in medial aspect (Fig. 39C, F, J). A ventromedial keel is present on the medial lobe, but terminates at about the midpoint of the bulla. Ŋe dorsal crest of the involucrum is anteriorly high and sharp, and in dorsal aspect, it has a sinuous outline (Fig. 39C). Faint transverse creases occur on the medial and dorsal surfaces of the involucrum. Ŋe inner posterior prominence is dorsoventrally narrow and does not extend as far posteriorly as the outer posterior prominence; the outer posterior prominence is large and hemispherical (Fig. 39J). REMARKS AND COMPARISONS Ŋe tooth (UCMP 219162) is larger than all nonglobicephaline delphinids (including Orcinus Fitzinger, 1860 and Hemisyntrachelus Brandt, 1873 for the purposes of this study), including Tursiops it is also larger than the teeth of some globicephalines ( Feresa Gray, 1870, Grampus Gray, 1828, Orcaella Gray, 1866, Peponocephala Nishiwaki and Norris, 1966). In terms of size and morphology, UCMP 219162 compares best with teeth of the fossil globicephalines Hemisyntrachelus (Bianucci 1996) and Protoglobicephala mexicana Aguirre-Fernández, Barnes, Aranda-Manteca &Fernández-Rivera, 2009. UCMP 219162 further differs from Grampus in having an elongate root with a closed pulp cavity; the roots of the few mandibular teeth of Grampus remain open during ontogeny (Boessenecker, pers. obs.). UCMP 219162 differs from Delphinapterus in lacking a curved root. Although teeth of the eastern North Pacific monodontid Denebola brachycephala Barnes, 1984 were not described or figured by Barnes (1984), the morphology of UCMP 219162 suggests that it does not belong to a monodontid. UCMP 219162 is similar in size and morphology to Globicephala macrorhynchus Gray, 1846, and Globicephala melas Traill, 1809, and substantially smaller than teeth of Pseudorca Reinhardt, 1862 and Orcinus . Although it lacks the more extremely developed anteroposterior root compression of Pseudorca and Orcinus , UCMP 219162 is similar in tooth morphology to Globicephala Lesson, 1828 and Protoglobicephala Aguirre-Fernandez, Barnes, Aranda-Manteca & Fernandez-Rivera, 2009, and is tentatively identified as an indeterminate globicephaline. Because of the large size of the tympanic bulla, UCMP 219034 cannot be identified as a small odontocete like Parapontoporia (see below), any fossil or extant phocoenid, or any small-bodied delphinid (e.g., Tursiops and all other non-globicephaline delphinids), although it is within the size range of globicephaline delphinids (e.g., pilot whales) as well as the beluga, Delphinapterus . Ŋis specimen differs from the enigmatic delphinoid Albireo whistleri in being transversely narrower with a transversely narrower involucrum with a sinuous (rather than straight) lateral margin; furthermore, Albireo whistleri exhibits a convex medial margin of the involucrum (straight in UCMP 219034), and an inner posterior prominence that extends as far posterior as the lateral posterior prominence. UCMP 219034 differs from Denebola brachycephala , Delphinapterus , and Monodon Linnaeus, 1758 in lacking a ventral surface of the bulla that is dorsally arched in medial and lateral view. UCMP 219034 further differs from Denebola Barnes, 1984 in being transversely narrower in ventral view, and possessing an inner posterior prominence that is transversely narrower and does not extend as far posteriorly as the outer posterior prominence. UCMP 219034 further differs from Delphinapterus in having a larger and more spherical outer posterior prominence, and in lacking an elongate ridge confluent with the inner posterior prominence on the medial surface. Because of these differences, UCMP 219034 is not identifiable as a monodontid. UCMP 219034 exhibits one delphinid synapomorphy, a ventromedial keel of the tympanic bulla that terminates near the midpoint of the bulla (Geisler & Sanders 2003). UCMP 219034 differs from Orcinus , Globicephala , and Pseudorca in its smaller size, but is larger than Grampus and Orcaella (Fig. 39). Ŋe anterior inflation of the involucrum appears to characterize monodontids and most delphinids, except Orcinus and Orcaella . UCMP 219034 lacks the prominent anterior spine which characterizes Globicephala and Grampus . Although similar in involucral morphology, this specimen differs from the extinct delphinids Arimidelphis sorbinii Bianucci, 2005, P. mexicana , Hemisyntrachelus oligodon Pilleri & Siber, 1989, and Hemisyntrachelus cortesii Fischer, 1829 in having a more posteriorly projecting outer posterior prominence (Pilleri & Siber 1989a; Bianucci 1996; Bianucci 2005; Aguirre-Fernández et al. 2009). UCMP 219034 shares a large and spherical outer posterior prominence with Pseudorca and Globicephala , which is lacking in Delphinapterus , Grampus , Orcinus , and non-globicephaline delphinids. Although being slightly smaller in absolute size, this specimen shares the most similarities among all globicephalines with Pseudorca however, given the uncertain diagnostic utility of isolated odontocete bullae, UCMP 219034 is only tentatively identified to the subfamily Globicephalinae. UCMP 219034 and 219162 appear to represent additional (albeit fragmentary) records of globicephalines from the Pliocene of the eastern North Pacific along with Protoglobicephala from Baja California (Aguirre- Fernández et al. 2009). Additional globicephaline fossils from the Santa Cruz section of the Purisima Formation including a partial skull (UCMP 219233) and two petrosals (UCMP 219487 and 219488) were reported by Boessenecker et al. (2013). Nevertheless, globicephalines appear to be relatively rare in Late Neogene strata of the eastern North Pacific. : Published as part of Boessenecker, Robert W., 2013, A new marine vertebrate assemblage from the Late Neogene Purisima Formation in Central California, part II: Pinnipeds and Cetaceans, pp. 815-940 in Geodiversitas 35 (4) on pages 886-888, DOI: 10.5252/g2013n4a5, http://zenodo.org/record/4538200 : {"references": ["BIANUCCI G. 1996. - Ne Odontoceti (Mammalia, Cetacea) from Italian Pliocene. Systematics and phylogenesis of Delphinidae. Palaeontolographica Italica 83: 73 - 167.", "GEISLER J. H. & SANDERS A. E. 2003. - Morphological Evidence for the Phylogeny of Cetacea. Journal of Mammalian Evolution 10 (1 / 2): 23 - 129.", "BIANUCCI G. 2005. - Arimidelphis sorbinii a new small killer whale-like dolphin from the Pliocene of Marecchia River (Central eastern Italy) and a phylogenetic analysis of the Orcininae (Cetacea: Odontoceti). Rivista Italiana di Paleontologia e Stratigrafia 111: 329 - 344.", "PILLERI G. & PILLERI O. 1989 A. - Balaenoptera siberi, ein neuer balaenopterid (Cetacea) aus der Pisco- Formation Perus I, in PILLERI G. (ed.), Beitrage zur Palaontologie der Cetacean Perus. Hirnanatomisches Institut der Universitat Bern, Ostermundigen: 63 - 106.", "BOESSENECKER R. W., PERRY F. A. & GEISLER J. H. 2013. - Globicephaline whales from the Mio-Pliocene Purisima Formation of central California, USA. Acta Palaeontologica Polonica. http: // dx. doi. org / 10.4202 / app. 2013.0019"]}